The Spenser encyclopedia - Hamilton, A. C. (Albert Charles), 1921-2016. (Toronto [Ont.] : University of Toronto Press, 1990)
Encyclopedia covers aspects of literature and society in Elizabethan England.
Book Cover; Half-Title; Series-Title; Title; Copyright; Contents; Direction for use; Classification of Articles; Introduction; Acknowledgements; Contributors; The Spencer Encyclopedia; A-Z; Illustrations; General Bibliography; Index.
Includes bibliographical references (pages 789-809) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Spenser, Edmund, -- 1552?-1599 -- Encyclopedias; Spenser, Edmund, -- 1552?-1599 -- Encyclopédies.; Spenser, Edmund, -- 1552?-1599; Spenser, Edmund -- 1552-1599; Spenser, Edmund; Poets, English -- Early modern, 1500-1700 -- Biography -- Encyclopedias; Great Britain -- Civilization -- 16th century -- Encyclopedias; Grande-Bretagne -- Civilisation -- 16e siècle -- Encyclopédies.; LITERARY CRITICISM -- Shakespeare; HISTORY -- Renaissance; POETRY -- English, Irish, Scottish, Welsh; Civilization; Poets, English; Poets, English -- Early modern; Great Britain; Wörterbuch; English poetry; e-books.; encyclopedias; Reference works; Encyclopedias; Encyclopedias; Reference works; Livres numériques.; Ouvrages de référence.; Encyclopédies.